SEQUENCE STRATIGRAPHIC STUDY AND SEISMIC IMAGING OF PLIOCENE LOWSTAND DEPOSITS IN OFFSHORE VIETNAM - Van Phung, Phong (Bulletin of Earth Sciences of Thailand, 2021)
Channels and basin floor fans are not only excellent evidences for analyzing the lowstand system tract but also common objectives in the oil and gas industry. Incised valleys or channel cuts and basin floor fans of this study area were observed and interpreted based on general 3D seismic data. Combining of seismic attributes and well data are used to predict their distributions as well as their lithology. In addition, evolutions of channels and basin floor fans through time were determined by using time slices or horizon slices of the seismic attribute cube association by shifting a window above a surface and displaying it as the RMS (root mean square) of amplitude over a specific interval. This study concentrated on sequence stratigraphy in terms of combining all data such as seismic and well log data to understand the processes and depositional environments of sequences. The sequences were interpreted by looking for channels or incised valleys and basin floor fans development from Pliocene to Recent time of this area. This research also discussed about primal factors, which affect depositional principles. There are relationships of relative sea level, sediment loading and subsidence rate to these sequences. In addition, relative ages of sequence S3 and S4 could be correlated with the published sea level curve of Wornardt et al., 2001. Channels and basin floor fans are displayed on the Gross Depositional Environment map. The maps are used to demonstrate the processes controlling the channels and basin floor fans.